Development of a computer software for the monitoring of subsidence - Othman, Rusli; Setan, Halim (2004)
A computer software has been developed at the Faculty of Geoinformation Science and Engineering, UTM for the purpose of detecting subsidence of ground surface or manmade structure by using Visual Basic 6.0 and FORTRAN computer languages. This software can be used for processing data from GPS and precise levelling methods. The software requires GPS baseline vectors (∆X, ∆Y, ∆Z). Relative ellipsoidal heights based on the WGS84 ellipsoidal surface must be derived from these baseline vectors. The derived relative ellipsoidal heights are then adjusted using least square estimation method. The adjusted heights will be used for further subsidence analysis. Stransformation is used to transform results from least square estimation using minimum constraints to a selected datum. This paper examines the method of subsidence using the iterative weighted transformation. In this method, the stability of reference points must be checked through a single point test. Stable points will then be adjusted again together with object points. Lastly, the stability of object points will be determined. User of this software requires little knowledge on deformation monitoring processing, as the user needs to follow the procedure of inputting data required by the software. The output from the software will give the stability of the all control points whether they have moved or otherwise.